Role of Oropharyngeal Administration of Colostrum in Very Low Birth Weight Infants for Reducing Necrotizing Enterocolitis: A Randomized Controlled Trial - Sharma, Deepak; Kaur, Amandeep; Farahbakhsh, Nazanin; Agarwal, Sunil (American Journal of Perinatology, 2020)
Objective This study aimed to study the role of oropharyngeal administration of colostrum (OAC) in very-low-birth-weight infants for reducing necrotizing enterocolitis (NEC).Study Design In this randomized controlled trial, 117 infants were enrolled, 59 were randomized to OAC group and 58 to routine care group. Infants with birth weight ≤ 1,250 g and/or gestational age ≤ 30 weeks were enrolled. Infants in OAC group received maternal colostrum (0.2 mL), 0.1 mL on either side, after 24 hours of postnatal life and were given every 2 hour for the next 72 hours irrespective of the enteral feeding status of the neonate. The primary outcome of the study was the incidence of NEC (stage 2 or 3).Results Baseline characteristics were comparable between the two groups. There was no significant reduction in the incidence of NEC in OAC group (0 [0%] vs. 3 [7.1%]; p = 0.11). There was significant reduction of 7 days of hospital stay in OAC group (34.2 ± 5.7 vs. 41.5 ± 6.7 days; p = 0.04).The incidence of early-onset sepsis, late-onset sepsis, blood culture positive sepsis, and ventilator-associated pneumonia were comparable between the two groups.Conclusion OAC is safe and reduces the duration of hospital stay.
Keywords: duration of hospital stay; necrotizing enterocolitis; oropharyngeal administration of colostrum; very low birth weight